2022
DOI: 10.1007/s00590-022-03306-y
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable factors influencing length of stay after total knee arthroplasty

Abstract: Purpose This cohort study aims to investigate the current Rapid-Recovery-(RR)-pathway at an orthopaedic surgery hospital centre and to identify preoperative, intraoperative, and postoperative factors that are significantly associated with prolonged hospital Length of Stay (LOS) after total knee arthroplasty (TKA). Method A total of 194 patients undergoing primary TKA were included in this retrospective study. Sociodemographic data documented were age, gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Previous studies have also explored the impact of preoperative complications on postoperative outcomes and have obtained conclusions similar to those of our study [32]. For example, Missmann, M. et al conducted a retrospective study involving 194 patients undergoing primary knee arthroplasty and found that preoperative complications such as a history of diabetes, hypertension, or cancer did not affect the length of patients' postoperative hospital stays [33]. One possible explanation for this result is that, although there were differences between the two groups, the absolute numbers of patients with a history of stroke, previous surgeries, and heart disease were all relatively small in this study.…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies have also explored the impact of preoperative complications on postoperative outcomes and have obtained conclusions similar to those of our study [32]. For example, Missmann, M. et al conducted a retrospective study involving 194 patients undergoing primary knee arthroplasty and found that preoperative complications such as a history of diabetes, hypertension, or cancer did not affect the length of patients' postoperative hospital stays [33]. One possible explanation for this result is that, although there were differences between the two groups, the absolute numbers of patients with a history of stroke, previous surgeries, and heart disease were all relatively small in this study.…”
Section: Discussionsupporting
confidence: 80%
“…Modifiable factors associated with successful early discharge include non-smoking status, independent preoperative ambulation, and presence of a postoperative caregiver [ 9 ]. On the other hand, higher prevalence of medical comorbidities, lower hemoglobin levels, requirement of blood transfusion(s), planned discharge to a rehabilitation facility, and truancy of preoperative patient education were associated with longer length of hospital stay [ 10 ]. For non-modifiable factors, male sex and married status were associated with shorter time to successful discharge whereas African-American ethnicity was associated with longer length of stay [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The risks of complications and costs associated with convalescence are significant. There is an established need for optimizing recovery and reducing risks associated with knee arthroplasty ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%